2017
DOI: 10.2139/ssrn.3051767
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Organizations in Regime Complexes: A Social Network Profile of IPBES

Abstract: Regime complexes are arrays of institutions with partially overlapping mandates and memberships. As tensions frequently arise among these institutions, there is a growing interest geared to finding strategies to reduce them. Insights from regime theory, science and technology studies, and social network analysis support the claim that ''boundary organizations''-a type of organization until now overlooked in International Relations-can reduce tensions within regime complexes by generating credible, legitimate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 82 publications
0
11
0
1
Order By: Relevance
“…In the parlance of social network analysis, a boundary organization that aspires to generate credible, legitimate, and salient knowledge requires both external "bridging ties," which connect it with various issue areas, scales, and epistemologies, as well as internal "bonding ties" (Coleman, 1988) to create a dense, balanced, and cohesive group. As a result, a third condition for a boundary organization to succeed, particularly salient at the international level, seems to be related to the social capital of its members, related to their professional and personal contacts, to their past professions, and their social networks (Morin, Louafi, Orsini, & Oubenal, 2017). Ideally, a boundary organization would include individuals from different functions and disciplines but also with different types of social capital, and would work with the aim of giving them an equal chance to express their views.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the parlance of social network analysis, a boundary organization that aspires to generate credible, legitimate, and salient knowledge requires both external "bridging ties," which connect it with various issue areas, scales, and epistemologies, as well as internal "bonding ties" (Coleman, 1988) to create a dense, balanced, and cohesive group. As a result, a third condition for a boundary organization to succeed, particularly salient at the international level, seems to be related to the social capital of its members, related to their professional and personal contacts, to their past professions, and their social networks (Morin, Louafi, Orsini, & Oubenal, 2017). Ideally, a boundary organization would include individuals from different functions and disciplines but also with different types of social capital, and would work with the aim of giving them an equal chance to express their views.…”
mentioning
confidence: 99%
“…The context in which boundary concepts are developed at the international level is already populated by an extensively broad range of norms, principles, and rules. In this fragmented architecture, boundary organizations could play a great role, by reducing tensions between international regimes when their members are representatives of different alternative understandings, like the IPBES in the biodiversity field (Morin et al, 2017). Partnerships are also promising forms of boundary structures (Gupta, Pistorius, & Vijge, 2016).…”
mentioning
confidence: 99%
“…Scaled-up and centralized technology assessment could also contribute to resolving the inherent difficulty of defining and delineating the actual objects of regulation, which has been a consistent theme in the case studies above. In Global Policy (2019) International Biotechnology Regulation addition, a central organization at the science-policy interface could also enhance the effectiveness of regulatory responses through multiple, fragmented international institutions (Morin et al, 2016). The case studies above also suggest a number of specific policy implications.…”
Section: Discussionmentioning
confidence: 99%
“…Only with effective, transparent and credible knowledge brokers at the interfaces between different disciplines and societal sectors, decision-makers can be informed and different perspectives comprehensively integrated (Neßhöver et al, 2016;Morin et al, 2017;Sarkki et al, 2019). Network analyses can help to assess knowledge exchange flows within a given network and identify or evaluate knowledge brokers (Toikka, 2010;Crona and Parker, 2011;Weiss et al, 2012;Cvitanovic et al, 2017), as demonstrated by the presented analysis.…”
Section: Nefo As Knowledge Broker and Boundary Organizationmentioning
confidence: 92%